CRITICAL ANALYSIS OF THE MANAGEMENT OF ECONOMIC POTENTIAL OF THE TOURISM AND MINING SECTORS IN LUMAJANG REGENCY - Suyono, Aji Prasetyo; Chandra, Yulian Ade; Sumardi, Umar (Sekolah tinggi ilmu ekonomi pemuda, 2024)
Lumajang Regency, located in East Java, has abundant natural resources and has enormous economic potential from the tourism and mining sectors for regional development. However, despite its enormous potential, Lumajang continues to struggle with economic stagnation and social inequality. This shows that the management of its regional potential is still not optimal. This study aims to critically examine the factors that inhibit the effectiveness of regional potential management in Lumajang Regency. This research is a qualitative descriptive study. The samples in this study are various information such as statistical data, qualitative research results, and various other sources of information to be further analyzed synthetically. To improve the economy of the Lumajang community in the tourism sector, the local government can use eight stages to determine the process of developing new products to be implemented in the tourism sector. Regional revenue from the mining sector has also not been able to dominate Locally-Generated Revenue (PAD) revenue and improve the economy of the Lumajang Regency community. Lumajang Regency has not yet maximized its two greatest potentials, namely the economic potential from the tourism and mining sectors. There are still many shortcomings that have not been solved in these two sectors.